2021
DOI: 10.3389/fevo.2021.607660
|View full text |Cite
|
Sign up to set email alerts
|

China's Legalization of Domestic Rhino Horn Trade: Traditional Chinese Medicine Practitioner Perspectives and the Likelihood of Prescription

Abstract: Despite the international ban on the trade of rhino horn that has been in place since 1977, persistent demand for horn in Asia has driven a spike in poaching over the past decade. This has embroiled the conservation community in a debate over the efficacy of banning trade relative to other solutions. Proposals for trade to be legalized and supplied through the dehorning of live rhinos or the production of synthetic horn are contentious. The need for empirical research into the potential impacts of legalization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 65 publications
1
5
0
Order By: Relevance
“…Unlike previous studies, this article adopts a multi-year scale approach to discuss the overall structural evolution of global TCM trade from a more macroscopic perspective. Similar to the findings by Hinsley et al ( 17 ) and Cheung et al ( 18 ), this article proceeds from the perspective of complex network and draws conclusions, including scale-free characteristics and shift of focus of import and export in the global trade of TCM products, asserting the existence of dependence and competition among countries or regions. Unlike previous studies, the results of this study show that the global TCM trade network is a typical small-world network that is closely connected and continuously expanding.…”
Section: Conclusion and Discussionsupporting
confidence: 62%
“…Unlike previous studies, this article adopts a multi-year scale approach to discuss the overall structural evolution of global TCM trade from a more macroscopic perspective. Similar to the findings by Hinsley et al ( 17 ) and Cheung et al ( 18 ), this article proceeds from the perspective of complex network and draws conclusions, including scale-free characteristics and shift of focus of import and export in the global trade of TCM products, asserting the existence of dependence and competition among countries or regions. Unlike previous studies, the results of this study show that the global TCM trade network is a typical small-world network that is closely connected and continuously expanding.…”
Section: Conclusion and Discussionsupporting
confidence: 62%
“…Synthetic alternatives to donkey skin are an option in reducing the demand, however understanding Chinese consumer's and TCM practitioner's attitudes and willingness to use alternatives are imperative. In relation to the use of rhino horn in TCM, one study found that 39 per cent of practitioners interviewed were open to use synthetic horn for patient treatment (Cheung et al 2021). In the case of bear bile, a type of acid (UDCA) which gives bear bile its proposed medicinal benefits has been chemically synthesised, and large quantities are consumed in China, Japan and South Korea (Feng et al 2009).…”
Section: Recommendations For Reducing the Impact Of The Donkey Skin T...mentioning
confidence: 99%
“…Without addressing underlying factors behind such institutional challenges and ensuring the enabling conditions are in place, it is unlikely that any policy responses relating to wildlife conservation or COVID-19 will be effective. It also suggests further examination is needed around the feasibility and effectiveness of a wildlife trade ban in Vietnam, as articulated by international communities; given the lack of institutional readiness and the ineffectiveness of similar bans in other countries ( Roe et al, 2020 , Cheung et al, 2021 ). Even China, which implemented a wildlife trade ban after the COVID-19 pandemic, still faces problems operating wildlife trade regulations due to outdated lists on protected species, insufficient cross-sector collaboration, weak law enforcement on the farming and trading of species, and a lack of quarantine standards for wildlife not covered by the ban ( Xiao et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%